2005
DOI: 10.1136/ijgc-00009577-200505001-00005
|View full text |Cite
|
Sign up to set email alerts
|

Review of gemcitabine-based combinations for platinum-resistant ovarian cancer

Abstract: Gemcitabine, an analog of deoxycytidine, is an anticancer nucleoside with proven activity in different solid malignancies. The efficacy of gemcitabine as a single agent or as part of a combination treatment has been evaluated in several trials, and antitumor activity has been observed in patients with sensitivity and resistance to both platinum and paclitaxel. In this context, preclinical studies have shown that gemcitabine-based combinations increase the cytotoxic action of the treatment and can potentially o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…These characteristics make gemcitabine an attractive partner for combination with other cytostatic agents. 14 Our study showed that gemcitabine and vinorelbine combination is feasible. To our knowledge, this is the first study evaluating this combination in ovarian cancer.…”
Section: Discussionmentioning
confidence: 63%
“…These characteristics make gemcitabine an attractive partner for combination with other cytostatic agents. 14 Our study showed that gemcitabine and vinorelbine combination is feasible. To our knowledge, this is the first study evaluating this combination in ovarian cancer.…”
Section: Discussionmentioning
confidence: 63%